Student's handbook : electrical engineering studies / Zahari Abu Bakar ...[et al.] - Abu Bakar, Zahari; Muhamad, Nur Amalina; Othman, Norhalida; Abdul Majid, Masmaria; Othman, Hanunah; Noorezam, Maisarah (School of Electricall Engineering, 2020)
This handbook is written to provide guidance to all PKE students regarding study plans, academic rules, and student’s ethics that must be adhered to, for at least six semesters with us. I hope that everyone will have fun and enjoy this whole new experience to gain the best knowledge studying at PKE, UiTM Johor Branch Pasir Gudang Campus. If you have any inquiries, do not hesitate to ask me, academic advisor or any other PKE lecturers. We are more than happy to assist you